It's all in your head - Namukuta, Sonia Charity Sajjabi (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of short stories that delve into the multifaceted nature of death, with a specific emphasis on murder, violence, death and their profound aftermath, including themes of loss, grief, and trauma. These stories offer diverse perspectives, narrated by perpetrators, voiceless victims, and those left to pick up the shattered pieces. Additionally, some stories are seen through the eyes of those tasked with handling the bodies. Often set in unnamed locations, they delve into imaginary and fantastical worlds, while remaining grounded in recognisable situations and spaces. I draw inspiration from popular and genre fiction such as horror, crime fiction and true crime stories, but approach my writing from a psychological lens, employing stylistic experimentation to challenge readers' expectations. The power of silence is a recurring motif. Rather than focusing on unearthing facts or revealing the "truth" like crime fiction often does, my narratives delve into what isn't or at times cannot be told "” the unsayable. Some of my stories explore silence inherent in violence, grief, and the inability to articulate one's experience in the face of a violent act or a life prematurely ended. Others delve into the silence of untold stories and the dark secrets of the perpetrators. By exploring these contrasting perspectives, I aim to offer a nuanced exploration of death and its aftermath. The writing styles of Stephen Graham Jones, Lydia Davis, and Kuzhali Manickavel influence my work. Lydia Davis, known for her mastery of very short, flash fiction, ranging from single sentences to a paragraph or two, inspires me with her precise observations of the human condition. Her minimalist prose, carefully selecting and arranging words and sentences, encapsulates the power of less-is-more storytelling. Manickavel creates surreal yet tangible worlds, combining idiosyncratic, intense and eerie elements with unfiltered expression. Drawing from her ability to blur the lines between the surreal and the real, I infuse my stories with a sense of disquieting authenticity. Stephen Graham Jones stands out for his ability to explore morbid themes in a compelling and unconventional manner. His experimentation with horror fiction tropes, the visceral realism of his prose, and his complex characters inspire me to capture the unsettling feeling that something dreadful has occurred without explicitly detailing the facts and intricacies.
Keywords: Creative writing (Higher education) -- South Africa; Short stories, South African (English) 21st century; Books Reviews; Diaries Authorship